2015
DOI: 10.1097/qai.0000000000000624
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use and HIV Among Female Sex Workers and Female Prisoners

Abstract: Female sex workers (FSWs) and female prisoners experience elevated HIV prevalence relative to the general population because of unprotected sex and unsafe drug use practices, but the antecedents of these behaviors are often structural in nature. We review the literature on HIV risk environments for FSWs and female prisoners, highlighting similarities and differences in the physical, social, economic, and policy/legal environments that need to be understood to optimize HIV prevention, treatment, and policy resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(49 citation statements)
references
References 53 publications
0
49
0
Order By: Relevance
“…Even fewer interventions incorporated women-specific and/or trauma-informed content, but those that did achieved more compelling intervention effects on HIV-related outcomes. This finding reflects known gender differences in the medical, psychiatric, and social service needs (11, 59), longitudinal HIV treatment outcomes during and following incarceration (60, 61), and HIV risk behaviors (14, 57) of CJ-involved populations. To be gender-specific (and thereby culturally competent) for target audiences of CJ-involved women, interventions should incorporate HIV risk reduction strategies that center on achieving self-efficacy or empowerment and acknowledge relational factors like IPV that contribute to women’s HIV risk and care engagement.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Even fewer interventions incorporated women-specific and/or trauma-informed content, but those that did achieved more compelling intervention effects on HIV-related outcomes. This finding reflects known gender differences in the medical, psychiatric, and social service needs (11, 59), longitudinal HIV treatment outcomes during and following incarceration (60, 61), and HIV risk behaviors (14, 57) of CJ-involved populations. To be gender-specific (and thereby culturally competent) for target audiences of CJ-involved women, interventions should incorporate HIV risk reduction strategies that center on achieving self-efficacy or empowerment and acknowledge relational factors like IPV that contribute to women’s HIV risk and care engagement.…”
Section: Discussionmentioning
confidence: 62%
“…Women who are CJ-involved often experience extraordinary stigma related to their incarceration, substance use, commercial sex work, and other risk behaviors (14). Stigma can exacerbate health disparities to negatively affect health outcomes and also restrict access, limiting the potential for intervention delivery (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have indicated that women who trade sex have many risk factors for HIV acquisition and transmission, including physical, social, economic, and policy risk factors. 1013 HIV-positive women who trade sex may be particularly vulnerable to these risk environments and face a number of factors that fuel their engagement in sex trading and increase their risk of HIV transmission. 14,15 For example, regarding the physical risk environment, research has shown that women who trade sex are more likely than women who have not traded sex to have higher levels of alcohol and substance use and more frequently experience intimate partner violence, which may decrease their ability to engage in safe sex and increase their likelihood of contracting or transmitting HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence leaves no doubt that women are more vulnerable to HIV/AIDS than men (17,29,30). In this study "partner's condom refusal" was the main reason of condom non-use among women living with HIV/AIDS.…”
Section: Discussionmentioning
confidence: 83%